2002
DOI: 10.2337/diacare.25.6.971
|View full text |Cite
|
Sign up to set email alerts
|

Young Men With High-Normal Blood Pressure Have Lower Serum Adiponectin, Smaller LDL Size, and Higher Elevated Heart Rate Than Those With Optimal Blood Pressure

Abstract: OBJECTIVE -Three measures-heart rate, a global index of the influence of the autonomic nervous system on the heart; circulating concentrations of adiponectin, an adipose-specific protein; and C-reactive protein (CRP), a sensitive marker of inflammation-have been reported to be closely associated with insulin resistance. Patients with borderline hypertension are known to be more insulin resistant and dyslipidemic than those with normal blood pressure (BP). BP can be classified into three categories: optimal, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
147
2
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(169 citation statements)
references
References 43 publications
15
147
2
5
Order By: Relevance
“…In this study we found that both IAF and adiponectin were major correlates of plasma lipoproteins, in particular of LDL buoyancy (Rf) and HDL cholesterol concentrations, in keeping with other reports [31,34,64]. These relationships could be mediated by effects of adiponectin on hepatic lipase activity, which is increased in central obesity and insulin resistance states associated with the metabolic syndrome [65,66].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study we found that both IAF and adiponectin were major correlates of plasma lipoproteins, in particular of LDL buoyancy (Rf) and HDL cholesterol concentrations, in keeping with other reports [31,34,64]. These relationships could be mediated by effects of adiponectin on hepatic lipase activity, which is increased in central obesity and insulin resistance states associated with the metabolic syndrome [65,66].…”
Section: Discussionsupporting
confidence: 91%
“…Circulating adiponectin concentrations are correlated with insulin sensitivity [30,31], with low concentrations predicting a future decrease in insulin sensitivity in Pima Indians [33]. Furthermore, low adiponectin concentrations have been associated with a more atherogenic lipid profile [34] and have been shown to increase with thiazolidinedione administration [35,36]. Studies in animals also suggest that adiponectin could be an important determinant of insulin action.…”
mentioning
confidence: 99%
“…Our study demonstrates that in offspring of diabetic parents HDL-cholesterol correlates highly with adiponectin, an association previously reported in healthy [13,14], obese [47] and type 2 diabetic subjects [48]. The link between HDL-cholesterol and EDV that we demonstrate is well established: multiple studies show low HDLcholesterol is highly predictive of endothelial dysfunction in healthy and diabetic subjects [49][50][51][52][53], and in experimental models where HDL-cholesterol is raised acutely, EDV normalises [58].…”
Section: Discussionsupporting
confidence: 80%
“…In brief, after an overnight fast and the collection of baseline samples, Dextrose 0.3 g/kg was administered intravenously, followed 20 min later by the intravenous infusion of insulin 0.03 U/kg (Humulin R; Eli Lilly, Indianapolis, IN, USA). Samples were collected for insulin and glucose at 2, 3, 4, 5,6,8,10,12,14,19,22,23,24,25,27,30,40,50,60,70,80, 90, 100, 120, 140, 160 and 180 min following the dextrose and analysed using the Bergman's Minimal Model, a computer-based method to assess plasma insulin and glucose dynamics during an IVGTT. The minimum model for glucose disposal and insulin dynamics yields assessments of insulin secretion and sensitivity, including the insulin sensitivity index (S I ) and the glucose effectiveness index (S G ) also known as insulin-independent glucose clearance.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation